(untitled) (Orfeu, 2026)
The objective of this study was to present the validity indexes of the Protocol for Screening Musical Abilities (PSHM). It was based on the psychophysical method of paired comparison with descriptive and non-parametric analysis. Ten schools participated (public, private, indigenous, one talent center in Brazil and another one in Mexico - 563 students aged 6 to 12. Results: i) the binomial analysis showed a significant association (p<0.001) among the items, so there was an effect between the stimulus and the response by the individuals; ii) the exploratory factor analysis found three factors with indexes above 0.50 (well-represented factors); iii) Kendell’s correlation of 0.856 (p<0.001); iv) Cronbach’s alpha with moderate and positive values; v) split-half analysis with different conditions with significant difference (Wilcoxon 28849 (p < 0.001); and vi) the difference was significant among age, school year and institution (p = 0.012 <0.005). Therefore, there were satisfactory validity indices of the PSHM.